The variation of coverage and access to palliative care for cancer patients in eight European countries: an exploratory vignette approach - Nathan Shuftan; Mark Dayan; Sarah Scobie; Bee Wee; Antoniya Dimova; Elka Atanasova; Liubove Murauskiene; Coralie Gandré; Zeynep Or; Gonçalo Figueiredo Augusto; Triin Habicht; Kristina Köhler; et al. (BMC Palliative Care)
Abstract Background Palliative care aims to maintain quality of life and offer treatment and person-centred care options for people with serious end-stage illnesses and their families. The purpose of this exploratory study was to compare the statutory coverage and access to palliative care for adult services for people with cancer in 8 European countries using a vignette approach. Methods We used a patient vignette to examine coverage and access to palliative care services across Europe. The palliative care vignette describes a pathway based on guidance for best practices of palliative care patients with incurable cancer. The surveys accompanying the vignette were completed by health services researchers knowledgeable on palliative care, practitioners, government officials, or teams consisting of a health systems expert working together with practitioners. Results Completed vignettes were received from 8 countries: Bulgaria, Estonia, France, Lithuania, the Netherlands, Portugal, Sweden and England. Services provided for palliative care envisioned in the vignette’s pathway are, generally, covered by the statutory health systems. However, in some countries cost sharing exists for hospital stays, certain medicines and medical aids. Furthermore, coverage of social and financial assessments, home equipment and financial advice varied in nearly every country. Travel times to and availability of palliative care specialists were identified as challenges across nearly all countries. Organizational barriers, societal stigmas and knowledge gaps about what palliative care entails were also found to be areas in need of improvement. Conclusions The comparative research presented provides further insight how countries organise palliative care, how services are offered and what levels of access exist around Europe. Our study showed differences in the scope of coverage of and access to the care options in the vignette. While responses showed countries have basic levels of coverage and access to services provided, there were variations, such as availability of specialists or the extent travel and waiting times influence care delivery. Settings where patients receive services also varied. As the need for palliative care grows in the future, health ministries and insurers should be increasingly concerned with how to guarantee coverage of and access to this care, as well as aware of best practices among countries facing similar challenges.